Sewers replacement and new construction - Read, Geoffrey F. (Elsevier Butterworth-Heinemann, 2004)
Sewers: Replacement and New Construction is a detailed guide to the management and construction of new sewer systems. Different construction and replacement techniques, such as jacking, moling and ramming, are described and evaluated. The importance of proper site preparation and management is emphasised, and detailed guidance is given to pre-construction investigation as well as to managing traffic and public relations during the construction period.
Keywords: Sewerage -- Design and construction.; elektronické knihy; electronic books